2009
DOI: 10.1071/ea08181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postweaning growth and bulls selected for extremes in retail beef yield and intramuscular fat on progeny liveweight and carcass traits

Abstract: Abstract. The present study is a component of a multi-site experiment, using Bos taurus cattle generated at four locations across southern Australia, designed to examine postweaning growth pathways for progeny whose sires were extreme in retail beef yield and intramuscular fat. Treatment and interaction effects on beef production and meat quality were examined within and across sites. The present paper describes the effect of postweaning growth and sire carcass type on liveweight and carcass traits at the Hami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
13
2
1
Order By: Relevance
“…Effects on fatness are of obvious practical importance to meeting carcass specifications when targeting specific market end points. The findings here of greater fatness associated with faster growth are consistent with the results reported by Graham et al (2009) from the Victorian site of the Regional Combination experiment, and by McIntyre et al (2009) from the Western Australian site. Graham et al (2009) also cited further supporting evidence from previous studies, showing higher planes of nutrition resulting in increased proportions of fat in the carcass (Berg and Butterfield 1968;Coleman et al 1993).…”
Section: Effects Of Growth Treatmentssupporting
confidence: 82%
See 2 more Smart Citations
“…Effects on fatness are of obvious practical importance to meeting carcass specifications when targeting specific market end points. The findings here of greater fatness associated with faster growth are consistent with the results reported by Graham et al (2009) from the Victorian site of the Regional Combination experiment, and by McIntyre et al (2009) from the Western Australian site. Graham et al (2009) also cited further supporting evidence from previous studies, showing higher planes of nutrition resulting in increased proportions of fat in the carcass (Berg and Butterfield 1968;Coleman et al 1993).…”
Section: Effects Of Growth Treatmentssupporting
confidence: 82%
“…The findings here of greater fatness associated with faster growth are consistent with the results reported by Graham et al (2009) from the Victorian site of the Regional Combination experiment, and by McIntyre et al (2009) from the Western Australian site. Graham et al (2009) also cited further supporting evidence from previous studies, showing higher planes of nutrition resulting in increased proportions of fat in the carcass (Berg and Butterfield 1968;Coleman et al 1993). Robinson et al (2001) demonstrated a small effect on the finishing growth rate in favour of animals having slower growth during backgrounding and a tendency for those with higher backgrounding growth rates to have higher intramuscular fat levels.…”
Section: Effects Of Growth Treatmentssupporting
confidence: 82%
See 1 more Smart Citation
“…Although there were no significant differences, RBY-sired animals tended to have higher EMA than IMFsired animals and this could account for the remaining difference in yield estimated using the VIAscan. These results were consistent with those of Graham et al (2009) andWilkins et al (2009) who also found differences in VIAscan estimates of RBY-and IMF-sired animals. As in the present study, RBYsired animals tended to have lower fat thickness and larger EMA.…”
supporting
confidence: 82%
“…comm. ) and Graham et al (2009) found similar differences in the palatability score estimated from the MSA model. The striploin of animals in the study of Wilkins et al (2009) were also subjected to the MSA sensory taste panel.…”
supporting
confidence: 57%